Approximation of Scale Parameter of Inverted Gamma Distribution by TOM Modified - Abdul Ameer Kuttar, Jubran (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The purpose of this research is to find an approximation to the scale parameter of inverted gamma distribution, where other parameter (shape parameter) is known, and compare it with several methods, where we found the preference of TOM by using Mean Square Error (MSE) to specify the best approximate to scale parameter in different samples size.